2021
DOI: 10.23797/2159-6719_24_8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variables affect the diversity of adult damselflies (Odonata: Zygoptera) in western Amazonia

Abstract: Our study evaluated the effects of environmental variables on the assemblages of the suborder Zygoptera, and tested the hypothesis that environmental variables are more important determinants of the structure of these assemblages than limnological variables in streams. We sampled 17 streams in the Carajás National Forest and tested our hypothesis using a linear regression analysis, with the zygopteran species composition, richness, and abundance as the response variables. Our findings indicate that both limnol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Odonata are an amphibious insect order (with aquatic nymphs and terrestrial adults) widely used as ecological indicators of freshwater ecosystem health [18][19][20][21]. Many studies showed that their assemblages are highly influenced by physicochemical water conditions [22][23][24][25][26] but even more importantly by habitat's morphology and structure (e.g., bottom substrate and structure of aquatic vegetation) [27][28][29][30][31][32][33]. Many Odonata species have life-history adaptations that enable them to occupy temporary habitats, such as desiccationtolerant eggs or fast larval growth [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Odonata are an amphibious insect order (with aquatic nymphs and terrestrial adults) widely used as ecological indicators of freshwater ecosystem health [18][19][20][21]. Many studies showed that their assemblages are highly influenced by physicochemical water conditions [22][23][24][25][26] but even more importantly by habitat's morphology and structure (e.g., bottom substrate and structure of aquatic vegetation) [27][28][29][30][31][32][33]. Many Odonata species have life-history adaptations that enable them to occupy temporary habitats, such as desiccationtolerant eggs or fast larval growth [34][35][36].…”
Section: Introductionmentioning
confidence: 99%